Effectiveness of PowerPoint-Based Digital Learning Media "Animals Education" in Terms of Retention Ability of Students - Sobri, Muhammad; Zain Amrullah, Lalu Wira; Indraswati, Dyah; Novitasari, Setiani (Jurnal Profesi Keguruan, 2025)
This study aims to examine the effectiveness of PowerPoint-based digital learning media "Animals Education" in improving the retention ability of Phase A students at SDN 1 Kuta, Central Lombok. This quasi-experimental study used quantitative data analysis. Data were gathered using tests and examined with paired sample t-tests, independent samples t-tests, N-gain analysis, and effect size tests. The findings are as follows: (1) The paired sample t-test for the experimental group showed a significance value of 0.000 < 0.05, indicating a significant difference in students' retention scores before and after the intervention; (2) the independent samples t-test showed a significance value of 0.000 < 0.05, suggesting a significant difference in retention between the experimental and control groups; (3) the N-gain score for the experimental group was 0.47, classified as moderate; (4) the effect size for the experimental group was 3.05, indicating that the use of digital "Animals Education" media is highly effective in enhancing student retention.